The overview of new carbon propeller development for 32kg gross weight agricultural multicopter (octocopter) - Kim, D.-K.; Wie, S.-Y.; Song, J.; Kang, T.; Kim, T.; Kee, Y. (My University, 2017)
This paper describes the general overview of new carbon propeller development for 32kg Gross Weight agricultural multicopter (Octocopter drone). Based on the design process of helicopter rotor blade, KARI conducted the carbon propeller development. All tools and facilities related to develop helicopter rotor blade were applied in this program. This paper shows the main research activities such as aerodynamic design and analysis, structural design and analysis, fabrication and investigation, ground and flight test. Finally the flight time of the multicopter using the improved carbon propeller has increased compared to existing beachwood propellers by more than 20% through improved aerodynamic performance and reduced carbon propeller weight. This results was campaigned in 2015 Creative Korea-Exposition. Through this research, KARI had a good opportunity in drone industry to localize carbon propeller and improve drone performance.